Understanding Multidimensional Determinants of Disability-Inclusive Education : Lessons from Rwanda, Sierra Leone, and Zambia - World Bank (Washington, DC, 2022)
Children with disabilities undoubtedly face barriers within the education system, however they also face significant challenges within the broader ecosystem that can significantly undermine their and their family’s ability to pursue educational opportunities on par with their peers without disabilities. This study aimed to understand what key determinants beyond school-based factors shaped the experiences of children with disabilities and their families’ ability to support their educational participation in primary school through case studies in Rwanda, Sierra Leone, and Zambia. The report also includes findings from a short regional survey of parents’ and caregivers’ perceptions across Sub-Saharan Africa. The study explored factors such as: (1) parental aspirations and involvement in their child’s education; (2) stigma and attitudes about children with disabilities; (3) access to necessary supports such as assistive devices, learning materials, and personal assistance; (4) additional and out-of-pocket costs borne by families to support the educational participation of children with disabilities as compared to children without disabilities; (5) accessibility of community infrastructure and transportation; and (6) financial resources and government benefits available to families to support their child’s education.